Influence of the form of the proximal femur on its functional structure in dysplastic hip arthritis - Loskutov, Oleksandr; Oleynik, Oleksandr; Zub, Tatyana; Loskutov, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
Changes in the form of joint ends of bones in cases of dysplastic coxarthrosis (DCA) are caused by a rate of complications after total hip replacement. The form of the bone determines its structure. The purpose of the present work was to reveal regularities in the influence of the bone form on the functional structure of the proximal femur in DCA. The functional structure was estimated by 105 radiogrammes of dysplastic hip joints and 130 radiogrammes of normal hip joints. The following indices were studied: the cortical index, Singh’s index and Noble’s index. An analysis of the results revealed that specific functional reconstruction in DCA took place owing to the valgus direction of the total load vector in the hip joint and owing to the valgus direction of the femoral neck. The above reconstruction manifested itself with thickening of the cortical bone and narrowing of the medullary canal against a background of reconstruction in the trabecular structure of the metaphysis towards strengthening of the Adams’ arch and rarefaction in the great trochanter region.